Função sexual de mulheres com Fibromialgia - Silva, Rafaela de Melo (2023)
Sexuality is an integral part of the individual, and is influenced by physical and psychological factors. Fibromyalgia is a central sensitization syndrome that mainly affects women and the clinical condition involves the presence of pain, anxiety, depression, low self-esteem, and these factors can negatively influence the sexual function of this population. It is essential to deepen knowledge in this area in view of the impact of sexual dysfunction on the quality of life and well-being of women with fibromyalgia. Study 1: The aim of the study was to investigate the relationship between sexual function and central sensitization in women with Fibromyalgia. This is a cross-sectional observational study. An online questionnaire was used for data collection. The questionnaire consisted of 85 questions, including questions to assess female sexual response (Female Sexual Function Index), assessment of central sensitization (Central Sensitization Inventory) and assessment of the impact of Fibromyalgia (Fibromyalgia Impact Questionnaire). 337 participants were included, 75.7% of women had sexual dysfunction. Furthermore, the results showed an association between sexual dysfunction and central sensitization. In conclusion, the results showed that there is a high prevalence of sexual dysfunction among women with Fibromyalgia, with a positive association between sexual dysfunction and central sensitization, with desire being the most affected domain. Study 2: the objective of the study was to evaluate the influence of anxiety and depression on the sexuality of Brazilian women with Fibromyalgia, for this, a cross-sectional observational study was carried out through an online questionnaire that evaluated female sexual response (Female Sexual Function Index), anxiety and depression (Hospital Anxiety and Depression Scale). A total of 255 women with sexual dysfunction were included in the study, most of them had moderate alteration related to depression (39.6%) and severe alteration related to anxiety (43.5%). Furthermore, the results showed that anxiety and depression are associated with sexual dysfunction. It is concluded that sexual dysfunction among Brazilian women with Fibromyalgia is associated with anxiety and depression, and it is essential that a screening of sexual dysfunction be carried out among patients with depressive symptoms and who have Fibromyalgia, so that an integral approach is carried out, in order to improve their quality of life.